Perbandingan Metode ARIMA dan SARIMA Dalam Peramalan Jumlah Penumpang Bandara Provinsi Kepulauan Bangka Belitung - Febiola, Aulia; Dewi, Amelia; Fazarin, Fatia Maura; Ramadhani, Fitri; Khaffi, Muhammad Akbar; Akbar, Ridho; Dalimunthe, Desy Yuliana (Department of Mathematics, Universitas Negeri Gorontalo, 2024)
One of the transportation that is often used by people in Bangka Belitung to travel outside the area is airplanes. Judging from the data on the number of passengers at two airports in the Bangka Belitung Islands Province, the highest number of airplane passengers departing outside the region in April 2023 was 88,511 people. If there isan excessive increase in the number of passengers, it will have an impact on the quality of airport service levels and disrupt the stability of flight traffic. The purpose of this study is to compare the results of forecasting the number of passengers at the airport of Bangka Belitung Islands Province for the future period using the ARIMA and SARIMA methods. Based on the results of the analysis, the best method to forecast the number of passengers at the Bangka Belitung Islands Provincial Airport is the ARIMA method with the best model, namely ARIMA (0,1,1). In general, the results of forecasting the number of passengers at the Bangka Belitung Islands Provincial Airport from May 2024 to April 2026 will increase the number of passengers continuously until April 2026.